2019
DOI: 10.1007/s00425-019-03228-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolite profiling of two switchgrass ecotypes reveals differences in drought stress responses and rhizosheath weight

Abstract: Main conclusion Rhizosheath comprises soil that adheres firmly to roots. In this study, two ecotypes of switchgrass with different rhizosheath sizes after drought stress were analyzed which showed metabolic differences under drought conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…Our results showed that OAs play an important role on the first day of salt stress. Similar to that which occurred in the present study, Liu et al [66] analyzed switchgrass under drought stress and found a large amount of AA and OA accumulation. Metabolomic analysis of buckwheat under salt stress also led to the same conclusion [49].…”
Section: Oas Are Correlated With Salt Stresssupporting
confidence: 89%
“…Our results showed that OAs play an important role on the first day of salt stress. Similar to that which occurred in the present study, Liu et al [66] analyzed switchgrass under drought stress and found a large amount of AA and OA accumulation. Metabolomic analysis of buckwheat under salt stress also led to the same conclusion [49].…”
Section: Oas Are Correlated With Salt Stresssupporting
confidence: 89%
“…Many studies over the past few decades have explored the response of plant roots to drought stress at the morphological, physiological, and molecular levels (Bartels and Sunkar, 2005; Xiong et al, 2006; Akpinar et al, 2015). Cereals and some other grass species form rhizosheath to ensure their successful adaptation to drought environments (George et al, 2014; Delhaize et al, 2015; Adu et al, 2017; Liu et al, 2019a; 2019b). The rhizosheath is a modification of the rhizosphere and is employed by plants as a drought tolerance strategy.…”
Section: Introductionmentioning
confidence: 99%
“…This root–soil contact surface has been described as an interesting interaction region between plants and the soil environment. The rhizosheath largely forms in drying soil and requires the presence of root hairs and mucilage to aggregate the soil particles together (Liu et al, 2019a). The mucilage is secreted from roots or bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations